Bibliometric Analysis of Work Life Balance on Employee Performance - Laudza, Ulwan Taqi (Westscience Press, 2025)
The purpose of this research is to learn more about matters related to an employee's work and personal life, including work-life balance, time balance, and satisfaction balance. For the literature analysis in this study, the Science Direct database was used to screen articles published from 2015-2025 through a bibliometric study. 412 articles were found according to the predefined criteria with keywords such as work-life balance and health. Data were analyzed using Vosviewer. The results explain how to analyze Co-authorship, Co-occurrence, and Citation. It is hoped that this research will be useful for further research on the issue of work-life balance (also known as work-life balance).